PENDAMPINGAN KREATIVITAS DAN SENI ANAK MELALUI KOLASE KUPU-KUPU DARI BEBIJIAN PADA ANAK USIA DINIDI TKK ADE IRMA SURYANI AIMERE - Maria Susanti Anu; Maria Enjela Mola, Antonia Sriyanti Sandeng, Angelina Kurnia Juita (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
Early childhood creativity and art mentoring is very important to develop, because early age is the golden age, which is the foundation for development in the next age. One of the ways to develop children's creativity and art is through collage activities. Collage activities include innovative activities and use more interesting materials. Creativity is the ability to create or develop something new based on ideas and concepts that are combined to become new, better and more useful works. Collage is one of the activities to improve the creativity of children aged 5-6 years and an innovative and interesting learning activity for children. The type of research used is qualitative descriptive research. The subjects of the study were children in group B at Tkk Ade Irma Suryani Aimere, totaling 23 children. Problems related to the lack of creativity and art in children. The data collection methods used were observation, interviews and documentation of the results of the work.